2021
DOI: 10.3390/jcm10143104
|View full text |Cite
|
Sign up to set email alerts
|

5-HTT Deficiency in Male Mice Affects Healing and Behavior after Myocardial Infarction

Abstract: Anxiety disorders and depression are common comorbidities in cardiac patients. Mice lacking the serotonin transporter (5-HTT) exhibit increased anxiety-like behavior. However, the role of 5-HTT deficiency on cardiac aging, and on healing and remodeling processes after myocardial infarction (MI), remains unclear. Cardiological evaluation of experimentally naïve male mice revealed a mild cardiac dysfunction in ≥4-month-old 5-HTT knockout (−/−) animals. Following induction of chronic cardiac dysfunction (CCD) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…In support of this observation is a study demonstrating that expression of inflammatory cytokines can be upregulated in the myocardium of Sert -/mice after experimental myocardial infarction. By contrast, there were no differences observed in non-operated mice (50). Furthermore, it has been shown in a mouse model of chemically induced colitis that SERT deficiency can increase infiltration of inflammatory cells into the mucosa and submucosa (51).…”
Section: Discussionmentioning
confidence: 81%
“…In support of this observation is a study demonstrating that expression of inflammatory cytokines can be upregulated in the myocardium of Sert -/mice after experimental myocardial infarction. By contrast, there were no differences observed in non-operated mice (50). Furthermore, it has been shown in a mouse model of chemically induced colitis that SERT deficiency can increase infiltration of inflammatory cells into the mucosa and submucosa (51).…”
Section: Discussionmentioning
confidence: 81%
“…Herein, following a 24-h incubation with 5-HTP, MMP14 and MMP2 , were downregulated by the 200 μM 5-HTP dose and tended to be upregulated by the 50 μM 5-HTP dose, respectively. Induced heart attack in 5-HTT (serotonin transporter) knock out models displayed an upregulated expression of MMP2 in the heart 43 . These authors postulate the 5-HT deficiency to be responsible for an impaired healing of the heart muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes have also been identi ed to be associated with MI, such as Nppa, Serpina3n, and Anxa1, which are signi cantly altered after MI [11]. Recent studies have shown that 5-HTT De ciency Affects Healing after Myocardial Infarction [12]. CTRP1 exacerbates cardiac dysfunction after myocardial infarction by regulating TLR4 in macrophages [13].…”
Section: Introductionmentioning
confidence: 99%